How to improve the production of peptidyl compounds in filamentous fungi - Umemura, Maiko; Tamano, Koichi (Frontiers in Fungal Biology, 2022)
Peptidyl compounds produced by filamentous fungi, which are nonribosomal peptides (NRPs) and ribosomally synthesized and post-translationally modified peptides (RiPPs), are rich sources of bioactive compounds with a wide variety of structures. Some of these peptidyl compounds are useful as pharmaceuticals and pesticides. However, for industrial use, their low production often becomes an obstacle, and various approaches have been challenged to overcome this weakness. In this article, we summarize the successful attempts to increase the production of NRPs and RiPPs in filamentous fungi and present our perspectives on how to improve it further.